Knowledge transfer in institutionalised supplier development and operational performance: the mediating role of absorptive capacity. Issue 1 (1st January 2021) - Sikombe, Shem; Phiri, Maxwell
Abstract: Organisations are increasingly relying on supplier development as a supply chain strategy to improve organisational performance through knowledge transfer. Prior research suggests that effective knowledge transfer requires absorptive capacity, allowing organisations to identify, assimilate and convert external knowledge into commercial value. The purpose of this paper is twofold. Firstly, to examine the effectiveness of knowledge transfer in institutionalised supplier development and, secondly, to examine the mediating effect of absorptive capacity on the relationship between knowledge transfer and operational performance. We used multiple hierarchical regression and mediation analyses using a bootstrapping procedure to analyse 171 responses from self-administered questionnaires from stratified randomly selected small and medium-sized local contractors in Zambia's construction industry. Findings reveal that knowledge transfer has a positive influence on the operational performance of local contractors. The study also found that knowledge transfer improves absorptive capacity, which significantly improves operational performance. The study shows that some of the dimensions of absorptive capacity do not significantly mediate the relationship. However, the relationship between knowledge transfer and the operational performance of local contractors is mediated by overall absorptive capacity. The paper contributes to understanding the role of absorption capacity in knowledge transfer and performance in the construction industry. Besides, the findings confirm that the effect of absorption capacity as a whole is more significant than its dimensions. Policy and managerial implications of the study findings have also been advanced.